(untitled) (Research, Society and Development, 2023)
The larynx is the organ that allows the passage of air to the caudal respiratory tract by controlling the air flow during the breathing process. Laryngeal paralysis consists of the unilateral or bilateral inability of the arytenoid cartilages to abduct during inspiration. It is a disorder that mainly affects elderly dogs of large to giant breeds and with congenital or acquired etiology, especially affecting breeds such as Bouvier des Flandres, Siberian Huskie, Bull Terrier, German Shepherd, Labrador, Golden Retriever, among others. Clinical signs include obstruction of the anterior airways during inspiration, exercise intolerance, inspiratory stridor and changes in vocalization, generating a weak and hoarse bark, in addition to choking and sporadic coughing. The diagnosis begins with clinical signs, physical examination, and is definitive by inspection of the laryngeal function by direct laryngoscopy or with the aid of an endoscope. Supportive treatment consists of stabilizing the patient with oxygen therapy and administering anti-inflammatory drugs. In animals with respiratory distress, emergency therapy should be instituted. Surgical treatment is the choice and consists of stabilizing and repositioning the arytenoid cartilages. This work aims to report a clinical case of a canine affected with laryngeal paralysis and describe the diagnostic investigation through direct laryngoscopy.